Musical achievement during a lockdown: the parental support miracle - Oliveira, António (2021)
The quality of parental support is recognized as a crucial factor in the early stages of a student’s development, and particularly in instrumental music education. At the start of 2020, the outbreak of a global pandemic crisis posed new and unprecedented challenges to education, forcing families to stay at home to prevent contagion. This investigation was conducted during the period of a COVID pandemic lockdown in Portugal. We explored whether parental support, provided during the lockdown period, was associated with their child’s achievement as reported by their instrumental music teacher. For this study, 39 parent–teacher dyads of first-grade students of an instrument music course were recruited from two public music conservatories. Parents supplied information on the frequency in which they provided student-support-related attitudes and actions in the home context. Simultaneously, teachers provided information about the student’s achievement during the lockdown compared with the previous in-person performance period. Results indicate a strong relationship between parental support and musical achievement, with students who received higher levels of supportive parental involvement performing better than before the pandemic crisis. The findings are discussed in relation to the importance of parental involvement in a child’s instrumental music education.